2013
DOI: 10.1063/1.4812366
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional flow structures in a moving droplet on substrate: A dissipative particle dynamics study

Abstract: It is of both fundamental and practical interest to study the flow physics in the manipulation of droplets. In this paper, we investigate complex flow in liquid droplets actuated by a linear gradient of wettability using dissipative particle dynamics simulation. The wetting property of the substrate ranging from hydrophilic to hydrophobic is achieved by adjusting the conservative solid-liquid interactions which results in a variation of solid-liquid surface tension. The internal three-dimensional velocity fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…It is found that there is faster transport of more hydrophilic microparticles. For A ls = −19, the travel time of droplet with a microparticle over the whole region with wettability gradient is almost same as that without the microparticle reported in our previous study 18. …”
supporting
confidence: 75%
See 1 more Smart Citation
“…It is found that there is faster transport of more hydrophilic microparticles. For A ls = −19, the travel time of droplet with a microparticle over the whole region with wettability gradient is almost same as that without the microparticle reported in our previous study 18. …”
supporting
confidence: 75%
“…This is because, for larger droplet, the difference of wettability across droplet is larger due to larger contact surface between droplet and substrate. 18 For R l ≥ 8, the effect on the manipulation of the microparticle from the droplet size becomes negligible. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 III.2.3 Effect on the transport of microparticle from the wettability of the microparticle As shown in Fig.…”
Section: Iii21 Effect On the Transport Of The Microparticle From Thmentioning
confidence: 98%
“…Recently the DPD method is modified to model the solid-liquid-gas co-existing systems, either by using the many body DPD approach developed by Warren [77] or by using a new conservative interaction potential with long-distance attraction and shortrange repulsion proposed by Liu et al [71], or by other approaches which are able to describe the attraction and repulsion between interacting DPD particles. For example, Li et al [91] investigated the 3D flow structures in a moving droplet on substrate by using the many body DPD, Zhang et al [92] studied the movement of a droplet in a grooved channel by using Liu's conservative interaction potential. Merabia and Pagonabarraga developed a mesoscopic model for simulating the dynamics of a non-volatile liquid on a solid substrate and they analyzed the kinetics of spreading of a liquid drop wetting a solid substrate and the dewetting of a liquid fill on a hydrophobic substrate [93].…”
Section: Micro Drop Dynamicsmentioning
confidence: 99%
“…These simulations are computationally demanding and require significant computing resources. In early exercises we used the DPD package [31] in LAMMPS [47]. The package takes advantage of the parallel computing readiness of LAMMPS and delivers satisfying scalability for homogeneous porous systems.…”
Section: Introductionmentioning
confidence: 99%